Peran Korps Wanita TNI sebagai Pasukan Pemeliharaan Perdamaian PBB dalam Humanitarian Assistance di Lebanon - Zulvyanie Pilgrimmy Firohmatillah; Arfin Sudirman (Indonesian Perspective, 2019)
This paper discusses about war and peace is one part of world history and an important phenomenon in International Relations. Since the end of the Cold War conflict not only occurs between countries but also intra-state so that non-state actors have an important role including the peace forces shaded by the United Nations Security Council. Indonesia is one of the contributing countries that sent peacekeepers to join the Garuda Contingent to Lebanon. The United Nations has carried out various peace operations which have also involved the participation of women’s forces which are also based on the Security Council Resolution 1325 of 2000. This research is aimed to understand the role of TNI Women as members of the Garuda Contingent who have been sent to Lebanon using the concept of peacekeeping operations and humanitarian assistance. This research attempts to describe the role of TNI Women in humanitarian assistance, which has been an important part of peace operations since resolution 1701 of 2006 issued by the United Nations Security Council.